Correlation Between Exercise Program With Lung Function And Achievements In Young Adult Swimmer - Diah Astini Paramita; Andi Wardihan Wardihan; Arif Santoso (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2020)
ABSTRACT This study aims to determine the correlation between exercise programs with lung function and swimming achievements of young adult athletes. Planning an exercise program by considering physiological stimulus encourages the body to adapt and improve lung function and maximize their performance. This is observational research used retrospective cohort study design. Sample in this study was selected based on the required criteria, 31 swimming athletes from the Indonesian Swimming Association of South Sulawesi and Swimming Club of Hasanuddin University, which are divided into two groups based on the presence or absence of the exercise program periodization that was implemented in the last 3 months. Data obtained through questionnaires and direct lung function examination using a spirometer. Based on the results of data analysis, it is known that there is a significant correlation between the exercise program and lung function, including Vital Capacity (VC), Force Vital Capacity (FVC) and Forced Expiratory Volume 1 second (FEV1) where the value of p <0.05. There is also a significant correlation between exercise program and swimming achievement where the value of p <0.01.